Facile synthesis of mesoporous SiO2 nanoparticles using the mobility differences of etchants. Issue 33 (13th March 2015) - Lee, Yi Seul; Jang, Wooree; Koo, Hye Young; Choi, Won San
Abstract : Mesoporous SiO2 nanoparticles (MSNPs): a novel approach for the synthesis of MSNPs that were prepared by treatment of styrene sulfonate monomer as an etchant on the SiO2 nanoparticles was demonstrated. Abstract : In this paper, we report the preparation of mesoporous silica nanoparticles (MSNPs) using the mobility differences of sulfonate or sulfate-containing materials as etchants. The MSNPs were synthesised by treating silica nanoparticles (SNPs) with styrene sulfonate (SS) or sodium dodecyl sulfate (SDS) under heat. The simple treatment of the SNPs with SS or SDS led to surface etching of the SNPs, resulting in surface roughening and pore generation within the silica structure. The surface structuring of the SNPs could also be controlled by varying the concentration of counter ions of the etchants. This one-step process is very simple, facile, and scalable. The MSNPs appeared almost transparent in an aqueous solution due to their unique surface morphology. The resulting MSNPs also exhibited excellent adsorption and desorption properties for toxic organic pollutants.